Efficient and automated large-scale detection of structural relationships in proteins with a flexible aligner - Gutiérrez, Fernando I.; Rodriguez-Valenzuela, Felipe; Ibarra, Ignacio L.; Devos, Damien; Melo, Francisco (BMC bioinformatics, 2016)
The total number of known three-dimensional protein structures is rapidly increasing. Consequently, the need for fast structural search against complete databases without a significant loss of accuracy is increasingly demanding. Recently, TopSearch, an ultra-fast method for finding rigid structural relationships between a query structure and the complete Protein Data Bank (PDB), at the multi-chain level, has been released. However, comparable accurate flexible structural aligners to perform efficient whole database searches of multi-domain proteins are not yet available. The availability of such a tool is critical for a sustainable boosting of biological discovery.